«ПОГРАНИЧНЫЙ ЯЗЫК» КАК ОСОБЫЙ ПЕРЕВОДЧЕСКИЙ ФЕНОМЕН (Филологические заметки, 2019)
Translation space conception is applied to the hierarchy of quality assessment criteria among witch harmony represents the highest level.
Keywords: translation, translation space, translation studies, intercultural communication, harmony.